Top management team nationality diversity, corporate entrepreneurship, and innovation in multinational firms - Boone, Christophe; Lokshin, Boris; Guenter, Hannes; Belderbos, René (Strategic Management Journal, 2019)
[Research Summary: We integrate insights from upper echelon theory and the literature on innovation and multinational corporations (MNCs) to develop a framework explaining when and why nationality diversity in top management teams (TMTs) affects corporate entrepreneurship—as evidenced by diversity in global knowledge sourcing—and through this innovation performance in MNCs. In a panel of 165 manufacturing MNCs based in 20 countries, we confirm that the positive effects of TMT nationality diversity on corporate entrepreneurship and innovation are only unleashed in TMTs with low social stratification and in MNCs located in home countries that are low in national power distance. Our study contributes to opening up the black box of the upper echelon's strategic role in spurring entrepreneurship and innovation in MNCs embedded in different cultures. Managerial Summary: The internationalization of TMTs in MNCs has been increasing in response to the globalization of markets and sources of knowledge. In this study, we examine under what circumstances MNCs that have TMTs comprised of executives with diverse nationalities exhibit stronger innovation performance. Analysis of leading corporations from 20 countries over a period of 10 years reveals that MNCs with diverse TMTs engage more in corporate entrepreneurship and subsequently see increased innovation performance—but only when these TMTs are operating in environments characterized by equal distribution of power and low hierarchy. The findings underscore the important role of corporate headquarters and TMT composition in the strategic management of modern MNCs.]